COVID‐19 is Feminine: Grammatical Gender Influences Danger Perceptions and Precautionary Behavioral Intentions by Activating Gender Stereotypes. Issue 2 (1st July 2021) - Mecit, Alican; Shrum, L. J.; Lowrey, Tina M.
Abstract : Gendered languages assign masculine and feminine grammatical gender to all nouns, including nonhuman entities. In French and Spanish, the name of the disease resulting from the virus (COVID‐19) is grammatically feminine, whereas the virus that causes the disease (coronavirus) is masculine. In this research, we test whether the grammatical gender mark affects judgments. In a series of experiments with French and Spanish speakers, we show that grammatical gender affects virus‐related judgments consistent with gender stereotypes: feminine‐ (vs. masculine‐) marked terms for the virus lead individuals to assign lower stereotypical masculine characteristics to the virus, which in turn reduces their danger perceptions. The effect generalizes to precautionary consumer behavior intentions (avoiding restaurants, movies, public transportation, etc.) as well as to other diseases and is moderated by individual differences in chronic gender stereotyping. These effects occur even though the grammatical gender assignment is semantically arbitrary.